Gender dynamics of Musheerabad fish market, Telangana, India - Mushkam, Priyanka; Sharma, Arpita (Indian Council of Agricultural Research, 2023)
Fish markets are integral components of the fisheries value chain and play a crucial role in livelihood development. A study was done with the objectives of assessing roles, time-use patterns, workload, constraints and fishery needs of women and men vendors of the Musheerabad fish market, Telangana, India. Our study employed a copyrighted tool developed by the Indian Council of Agricultural Research – Central Institute of Fisheries Education called the Gender Analysis Tool for Fisheries and Aquaculture (GATFA) which examines various dimensions of gender dynamics. A non-parametric Mann–Whitney U test was used to determine if significant differences existed between men and women. Rank based quotient (RBQ) was employed to assess severity of constraints. It was found that women are engaged in intensive reproductive roles (6.3 hours/day) alongside their market activities. For reproductive roles, significant differences were discerned between men and women in terms of time use and workload. Women spent 8.2 hours/day in fish markets which was more than their men counterparts (7.9 hours/day). Both genders were actively engaged in productive and community roles with no statistically significant differences in their time use and workload. Statistically significant differences were found between men and women with respect to fisheriesrelated needs. However, no significant difference was seen among men and women for practical and strategic gender needs. High operational costs and limited financial returns from fish sales were the main constraints for both. Economic constraints with a RBQ of 80.90 ranked first, followed by fisheries constraints. Improved market infrastructure, and access to credit and financial support are required. Our findings underscore the critical importance of gender-inclusive policies and interventions.